Anatomical Surgical Outcomes of Patients With Advanced Coats Disease and Coats-Like Detachments: Review of Literature, Novel Surgical Technique, and Subset Analysis in Patients With Facioscapulohumeral Muscular Dystrophy. (October 2019) - Rao, Prethy; Knapp, Austen N.; Todorich, Bozho; Drenser, Kimberly A.; Trese, Michael T.; Capone, Antonio
Abstract : Supplemental Digital Content is Available in the Text.